Processing of Emotional Faces in Patients with Chronic Pain Disorder: An Eye-Tracking Study - Giel, Katrin Elisabeth; Paganini, Sarah; Schank, Irena; Enck, Paul; Zipfel, Stephan; Junne, Florian (Frontiers in Psychiatry, 2018)
Objective: Problems in emotion processing potentially contribute to the development and maintenance of chronic pain. Theories focusing on attentional processing have suggested that dysfunctional attention deployment towards emotional information, i.e. attentional biases for negative emotions, might entail one potential developmental and/or maintenance factor of chronic pain. Methods: We assessed self-reported alexithymia, attentional orienting to and maintenance on emotional stimuli using eye tracking in 17 patients with chronic pain disorder (CP) and two age- and sex-matched control groups, 17 healthy individuals (HC) and 17 individuals who were matched according to depressive symptoms (DC). In a choice viewing paradigm, a dot indicated the position of the emotional picture in the next trial to allow for strategic attention deployment. Picture pairs consisted of a happy or sad facial expression and a neutral facial expression of the same individual. Participants were asked to explore picture pairs freely. Results: CP and DC groups reported higher alexithymia than the HC group. HC showed a previously reported emotionality bias by preferentially orienting to the emotional face and preferentially maintaining on the happy face. CP and DC participants showed no facilitated early attention to sad facial expressions, and DC participants showed no facilitated early attention to happy facial expressions, while CP and DC participants did. We found no group differences in attentional maintenance. Conclusions: Our findings are in line with the clinical large overlap between pain and depression. The blunted initial reaction to sadness could be interpreted as a failure of the attentional system to attend to evolutionary salient emotional stimuli or as an attempt to suppress negative emotions. These difficulties in emotion processing might contribute to etiology or maintenance of chronic pain and depression.